DNA damage tolerance in stem cells, ageing, mutagenesis, disease and cancer therapy. Issue 14 (28th June 2019) - Pilzecker, Bas; Buoninfante, Olimpia Alessandra; Jacobs, Heinz
Abstract: The DNA damage response network guards the stability of the genome from a plethora of exogenous and endogenous insults. An essential feature of the DNA damage response network is its capacity to tolerate DNA damage and structural impediments during DNA synthesis. This capacity, referred to as DNA damage tolerance (DDT), contributes to replication fork progression and stability in the presence of blocking structures or DNA lesions. Defective DDT can lead to a prolonged fork arrest and eventually cumulate in a fork collapse that involves the formation of DNA double strand breaks. Four principal modes of DDT have been distinguished: translesion synthesis, fork reversal, template switching and repriming. All DDT modes warrant continuation of replication through bypassing the fork stalling impediment or repriming downstream of the impediment in combination with filling of the single-stranded DNA gaps. In this way, DDT prevents secondary DNA damage and critically contributes to genome stability and cellular fitness. DDT plays a key role in mutagenesis, stem cell maintenance, ageing and the prevention of cancer. This review provides an overview of the role of DDT in these aspects.